TER HORST, Eleanor, Edward FRIEDMAN and Ali Shehzad ZAIDI (eds.) Studies in Honor of Robert ter Horst. Fair Lawn, NJ: Transformative Studies Institute Press, 2017. ISBN: 978-0-9832982-2-9, 185 pp. - López-Peláez Casellas, Jesús (Alfinge. Revista de Filología, 2019)
Estudio y reseña del libro editado por Eleanor ter Horst, Edward Friedman, y Ali Shehzad Zaidi Studies in Honor of Robert ter Horst. (Fair Lawn, NJ: Transformative Studies Institute Press, 2017).